Charge collection in irradiated HV-CMOS detectors - Hiti, B; Affolder, A; Arndt, K; Bates, R; Benoit, M; Di Bello, F; Blue, A; Bortoletto, D; Buckland, M; Buttar, C; Caragiulo, P; Das, D; et al. (Elsevier, 2018)
Active silicon detectors built on p-type substrate are a promising technological solution for large area silicontrackers such as those at the High Luminosity LHC, but the radiation hardness of this novel approach has tobe evaluated. Active n-in-p strip detector prototypes CHESS2 for ATLAS with different substrate resistivities inthe range of 20–1000Ωcmwere irradiated with neutrons and protons up to a fluence of2 × 1015neqcm−2and3.6 × 1015neqcm−2. Charge collection in passive test structures on the chip was evaluated using Edge-TCT andminimum ionising electrons from90Sr. Results were used to assess radiation hardness of the detector in the givenfluence range and to determine parameters of initial acceptor removal in different substrates.